2011
DOI: 10.1053/j.gastro.2011.06.082
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Structural and Functional Alterations in Infants and Children With Biliary Atresia, Listed for Liver Transplantation

Abstract: Background & Aims Cirrhotic liver diseases are associated with abnormalities in cardiac geometry and function in adults (cirrhotic cardiomyopathy), but rarely explored in cirrhotic infants or children. We proposed that features of cirrhotic cardiomyopathy are present in infants with cirrhosis due to biliary atresia (BA) as early as the time of evaluation for liver transplantation and will correlate with mortality and post-operative morbidity. Methods Two-dimensional echocardiography (2DE) of infants with BA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 38 publications
3
72
2
1
Order By: Relevance
“…These human experiments, which were faithfully reproduced in isolated adult mouse cardiomyocytes, further strengthen the long-held notion that high levels of circulating bile acids adversely affect myocardial cell biology. More importantly, these studies add clinical relevance to the animal studies which speculated a role for bile acids in the pathophysiology of cardiac dysfunction in cirrhosis,13 14 termed cirrhotic cardiomyopathy,15 16 which has a prevalence of ∼50% according to some studies 17 18. Electrocardiographic abnormalities, more specifically prolonged QT interval is a key derangement of cirrhotic cardiomyopathy and is known to cause sudden death in adults 19 20 and increases mortality risk in children21 with liver failure.…”
mentioning
confidence: 85%
“…These human experiments, which were faithfully reproduced in isolated adult mouse cardiomyocytes, further strengthen the long-held notion that high levels of circulating bile acids adversely affect myocardial cell biology. More importantly, these studies add clinical relevance to the animal studies which speculated a role for bile acids in the pathophysiology of cardiac dysfunction in cirrhosis,13 14 termed cirrhotic cardiomyopathy,15 16 which has a prevalence of ∼50% according to some studies 17 18. Electrocardiographic abnormalities, more specifically prolonged QT interval is a key derangement of cirrhotic cardiomyopathy and is known to cause sudden death in adults 19 20 and increases mortality risk in children21 with liver failure.…”
mentioning
confidence: 85%
“…A study in children with biliary atresia listed for liver transplant concluded that cardiomyopathy is a prevalent condition in infants with end-stage cirrhotic liver disease due to biliary atresia (> 70%) compared with age-matched controls without liver disease. 11 Furthermore, children with preexisting abnormal echocardiography had longer intensive care unit and hospital stays after transplant. A mouse model of CC demonstrated rapid development of cardiac hypertrophy and altered function, including impaired inotropic response within 3 weeks of inducing biliary fibrosis.…”
Section: Cardiac Derangements and Esldmentioning
confidence: 99%
“…It should be pointed out that the systemic pressure levels of the two groups were similar to normal values, also considering that all patients were chronically taking a beta-blocker in order to reduce portal pressure while waiting on the transplant line. These patients are known to have peripheral systemic vasodilation and increased cardiac output in a compensatory manner, a fact that seems to have been effective in these patients 6,17,18 .…”
Section: Analysis Of 83 Consecutive Liver Transplants Performed At a mentioning
confidence: 99%